A mercury(ii) ion sensor device based on an organic field effect transistor with an extended-gate modified by dipicolylamine. Issue 100 (14th October 2015) - Minami, Tsuyoshi; Sasaki, Yui; Minamiki, Tsukuru; Koutnik, Petr; Anzenbacher, Pavel; Tokito, Shizuo
Abstract : The detection of mercury(ii ) ions (Hg 2+ ) in water was successfully achieved by a disposable and reusable extended-gate organic transistor modified with an artificial receptor. Abstract : Herein, we report an organic field effect transistor (OFET) with an extended-gate modified by an artificial receptor for the detection of mercury(ii ) ions (Hg 2+ ) in water. The sensor device is easy to fabricate, reusable, disposable, and portable. Thus OFET sensors could be applied for low-cost on-site detection of Hg 2+ .